Radon Concentration in Coal Mining In Corrales- Boyacá (2023)
The concentrations of radon 222Rn can be quantified using active and passive measurements (in situ). This radioactive gas in enclosed spaces such as underground coal mines is a silent threat because inhaling it at high concentrations can induce lung cancer in workers exposed for extended periods. Currently, Colombia lacks protocols for the measurement and prevention of this radioactive gas. Therefore, the primary objective of this study is to measure the concentrations of 222Rn to which the workers in the El Volca ́n coal mine, located in the municipality of Corrales in the Boyaca ́ department of Colombia, are exposed. To achieve this, a radiological mapping was conducted inside the mine using nuclear track detectors placed within diffusion chambers. A total of 32 measurement points were monitored over a 60-day period, obtaining 222Rn activity concentrations rangingfrom700to2000 Bq·m−3.WhencomparedtothepermissiblelimitsrecommendedbytheICRP,thesemeasurements fall within the allowed range for enclosed spaces. These measurements were extrapolated to calculate the probability of radiological risk associated with lung cancer in this specific mine. In conclusion, the calculations show low concentrations of this radioactive gas, 222Rn, and consequently, low doses absorbed by the personnel.